2020
DOI: 10.1016/s0140-6736(20)31423-9
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic disparities in COVID-19 mortality: are comorbidities to blame?

Abstract: COVID19, it is very concerning that the case fatality at 30 days after hospital admission for COVID19 appears to be the same in Black and White patients. 2 The lack of association between ethnicity and COVID19 mortality after adjustment for comorbidities is not reassuring. This suggests that research into ethnic disparities in COVID19 mortality must consider social as well as biological factors.I declare no competing interests. I thank Roba Khundkar for her support and constructive criticism when writing thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 0 publications
0
37
0
2
Order By: Relevance
“…An analysis of 55 provinces capital in Italy recently revealed that increase in symptomatic COVID-19 infected cases was associated with variations in air pollution level (Coccia 2020). Also, other studies found that prevalence of comorbidities plays a key role in higher mortality of COVID-19 (Richardson et al 2020;Tian et al 2020;Ravi 2020). It also has been proven that some medical conditions like diabetes and heart diseases can increse the risk of death in COVID-19 patient (Richardson et al 2020;Coccia 2020).…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of 55 provinces capital in Italy recently revealed that increase in symptomatic COVID-19 infected cases was associated with variations in air pollution level (Coccia 2020). Also, other studies found that prevalence of comorbidities plays a key role in higher mortality of COVID-19 (Richardson et al 2020;Tian et al 2020;Ravi 2020). It also has been proven that some medical conditions like diabetes and heart diseases can increse the risk of death in COVID-19 patient (Richardson et al 2020;Coccia 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The differences between ethnic groups with lower scores for both feelings of safety and intention to participate in research and/or attend clinical appointments in our BAME responders is particularly relevant. The disproportionate risk of contracting COVID-19 (13) and poorer outcomes in BAME groups compared to white counterparts (14) is a recognised public health issue. Public Health England has engaged with key stakeholders to start the process of understanding this health inequality and discuss strategies to reduce the direct and indirect impact of this pandemic and indeed any future pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between ethnic groups with lower scores for both feelings of safety and intention to participate in research and/or attend clinical appointments in our BAME responders is particularly relevant. The disproportionate risk of contracting COVID-19 (13) and poorer outcomes in BAME groups compared to white counterparts (14) is a recognised public health issue. Public Health England has engaged with key stakeholders to start the process of understanding this health inequality and discuss strategies to reduce the direct Histograms for scales (not shown) showed there was a distinct grouping of respondents into those who felt safe and those who did not, with generally few people in the middle.…”
Section: Discussionmentioning
confidence: 99%